The Relationship of Coping Mechanisms and Mental Health After Breakup - Kiki Maharani; Ani Haryani; Dina Rahmawati; Deni Suwardiman; Intan Rizkianti; Yeni Biteriawati (KHD Production, 2024)
A person's coping mechanism in dealing with problems in life, whether problems with family, friends, or problems with a partner, can affect mental health conditions. Unstable mental health conditions in students can have an impact on their daily lives. This study aims to determine the relationship between coping mechanisms and mental health after a breakup. By using a cross-sectional approach, a sampling technique using purposive sampling and 101 respondents participated. Data collection using a coping mechanism questionnaire and mental health after a breakup questionnaire. The results showed that some respondents had adaptive coping mechanisms (53.5%) and good mental health (55.4%). The results of statistical analysis using the chi-square test showed a significant relationship between coping mechanisms and mental health (p value=0.001) and students with maladaptive coping mechanisms were 10 times more likely to experience poor mental health after they experienced a breakup. Efforts are needed to improve students' adaptive coping skills to prevent poor mental health problems when they experience a breakup.